Primary Prevention of Domestic Violence: Contributions of Curricular Practices to the Strengthening of Citizenship - Martins, Alcina Manuela Oliveira; Costa, Elisabete Pinto da (Fronteira: Journal of Social, Technological and Environmental Science, 2024)
At a global level, quality education is fundamental to achieve social and gender justice, stability, and sustainable development worldwide. Therefore, the education system is faced with the need to find answers to these challenges, which can result in multiple social violences. The investment in Portugal in an education for citizenship is based on the implementation of an educational policy that introduces, in an intentional and strategical manner, into the curriculum, fracturing themes in societies with the aim of its transformation. In this regard, the construction of the curriculum, as proposed by the Critical Theory, as a social practice, can constitute an educational strategy for the study and action on the problematic issue of primary prevention of domestic violence. The aim of this research is to understand to what extent the inclusion of the issue of domestic violence in curricular practices, in the context of citizenship education, contributes to the primary prevention of this social scourge. The methodological course of the research is based on a qualitative approach of exploratory nature, using a questionnaire with four open-ended questions. The study took place in two public schools, at the primary and secondary levels, in Oporto and in Lisbon. The former has a Prevention Project against Domestic Violence in place; the second has no similar project. The data were obtained using Google Forms tool. Eight participants were selected, four from each school, all teachers at the end of a schooling cycle, specifically: 4th year, 6th year, 9th year and 12th year. The study revealed that, in the school in Oporto, the implementation of the Violence Prevention Program, resulted in curriculum changes to meet social needs and requirements. In the school in Lisbon, on the other hand, since it was not implemented a Violence Prevention Program there were not significant curriculum changes, there being only awareness-raising on the subject.